Nilai Moral pada Novel “Alang” Karya Desi Puspitasari dan Implementasinya dalam Pembelajaran Sastra di SMA - Tusoleha, Wilda Amelia; Hikmat, Ade (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The current condition of language and literature learning is still not optimal. Therefore, the researcher conducted a study to examine moral values and their application in student learning in high school through the novel